AI-Driven Mobile Childrens Book Generator A Case Study of Tema Insani Psychology Consultancy - Pasha Catra Parama, Anak Agung Ngurah; Ayu Wirdiani, Ni Kadek; Dwi Rusjayanthi, Ni Kadek (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 13 No 1 (2025): Vol. 13, No. 1, April 2025DO - 10.24843/JIM.2025.v13.i01.p01, 2025)
The advancement of technology drivesving digitalization across various sectors, including psychology and literacy in Indonesia. This motivates children’s psychology consultant Tema Insani to enhance children’s literacy interest by considering psychological conditions, neurodevelopmental disorders, and developmental age, which have so far relied heavily on parents’ role in providing books. The issue presents a solution in the form of a mobile-based application that can generate bedtime stories tailored to children’s age, disorders, and preferences. The app includes a reading tracker to monitor children’s literacy progress based on reading frequency. The development uses the Agile methodology and Dart with Flutter SDK as the primary development language. The black box testing results show that using the app with children at night can increase reading frequency by replacing device usage with bedtime stories. The development of the app is expected to support Tema Insani’s efforts to bridge psychology, technology, and children’s literacy interest in Indonesia.